The Mid-Pleistocene Transition and the Vostok Oldest Ice Challenge - V. Ya. Lipenkov; D. Raynaud (Лëд и снег, 2015)
Marine records indicate a dramatic change in the predominant periodicity of climate variability, from about 40 ka to about 100 ka around one million years ago. The reason for this major climatic shift, which is called the Mid-Pleistocene Transition or MPT, remains unknown – and is of great interest to the climate scientist. Could the core of the oldest meteoric ice bedded at Vostok between 3310 and 3539 m, which has experienced severe deformation, nevertheless be useful in deciphering some of the aspects of the MPT enigma? Reflecting upon this question and considering the available data from the disturbed section of the ice core, we feel impelled to propose a new project focused on the oldest Vostok meteoric ice, which could be named the Vostok Oldest Ice Challenge or VOICE.